2021
DOI: 10.3390/e23091111
|View full text |Cite
|
Sign up to set email alerts
|

Improved YOLO Based Detection Algorithm for Floating Debris in Waterway

Abstract: Various floating debris in the waterway can be used as one kind of visual index to measure the water quality. The traditional image processing method is difficult to meet the requirements of real-time monitoring of floating debris in the waterway due to the complexity of the environment, such as reflection of sunlight, obstacles of water plants, a large difference between the near and far target scale, and so on. To address these issues, an improved YOLOv5s (FMA-YOLOv5s) algorithm by adding a feature map atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The performance of YOLOv2-tiny is clearly worse than that of YOLOv2, YOLOv3, and YOLOv3-tiny as small objects tend to be ignored by YOLOv2. This is likely due to the lack of multi-scale feature maps in YOLOv2 [73]. Previous research [59] found that YOLOv2 provides mAP 47.9 with average IoU 54.7 in the plastic detection compared to 0.809 at IoU 0.5 for YOLOv4 pre-trained here.…”
Section: Experiments I Ii Iii and Iv: Plastic Detection In Uav Imagerymentioning
confidence: 73%
“…The performance of YOLOv2-tiny is clearly worse than that of YOLOv2, YOLOv3, and YOLOv3-tiny as small objects tend to be ignored by YOLOv2. This is likely due to the lack of multi-scale feature maps in YOLOv2 [73]. Previous research [59] found that YOLOv2 provides mAP 47.9 with average IoU 54.7 in the plastic detection compared to 0.809 at IoU 0.5 for YOLOv4 pre-trained here.…”
Section: Experiments I Ii Iii and Iv: Plastic Detection In Uav Imagerymentioning
confidence: 73%
“…The system identified obstacles in front of users through the YOLOv5s network, effectively guiding visually impaired people to walk safely on sidewalks and crosswalks. Aiming at the problem of real-time monitoring of floating waste in the waterway [19], a FMA (feature map attention) layer was added to improve YOLOv5s, and splicing data enhancement technology was used to improve the training of small and medium-sized target detection effects. In the literature [20], the TR-YOLOv5s network and down sampling principle were proposed, and an attention mechanism was introduced to meet the highprecision and high-efficiency identification requirements for underwater targets.…”
Section: Related Workmentioning
confidence: 99%
“…On the one hand, there is cooperation with other methods, such as use YOLOv3 to extract and classify underwater objects and combine it with a deep learning method based on (Long Short Term Memory)LSTM to determine the location of the underwater objects [7]. On the other hand, the YOLO backbone structure is optimized [8], [9], such as replaced the output layer with deformable convolution to improve the detection speed in the backbone network CSPDarknet53_dcn(P) of YOLOv4. And a new feature fusion module was redesigned to improve the detection accuracy of small objects using multiple scale detection layers [10].…”
Section: Introductionmentioning
confidence: 99%